The Effectiveness of Animated Educational Videos in Reducing Anxiety Among Hospitalized Preschool Children - Hendra, Agus; Yusuf, Muhamad Rafhi (Jurnal Keperawatan Universitas Jambi, 2025)
Background: Hospitalization in children causes trauma and even feelings of anxiety. Especially in preschool children, this anxiety often occurs which can result in several undesirable things happening such as less than optimal healing process during hospitalization, and can even cause deep trauma for preschool children. Trauma from the pain that children have suffered makes children afraid to do it again, so nurses must be able to provide a technique to prevent this, for example, animated video distraction can be used as a medium to overcome this. Objective: This study aims to determine the effectiveness of animated videos in reducing the level of anxiety in preschool children during hospitalization. Method: This study was Quasy Experiment. The total sample were 60 respondents that sellected using using convenience sampling technique. The Spence Children's Anxiety Scale (SCAS) questionnaire was used to measure anxiety. Data analysis was using the Wilcoxon Signed Ranks Test and Mann-Whitney. Results: The results of the study showed that animated videos was effective to reducing the level of anxiety in preschool children during hospitalization with a p-value of 0.000. Conclusion: Animated videos are effective or influential in reducing the level of anxiety in preschool children during hospitalization. Keywords: